Handbook of narrative analysis - Herman, Luc; Vervaeck, Bart (University of Nebraska Press, 2019)
"Handbook of Narrative Analysis is the go-to book for understanding and interpreting narrative. Luc Herman and Bart Vervaeck have revised and extended the first edition by describing and applying the last fifteen years of cutting-edge scholarship in the field of narrative theory"- Resumé vydavatel
Keywords: naratologie; narativita; narratology; narratives; narativní analýza; monografie; příručky; monographs; handbooks and manuals